Superior mesenteric artery syndrome following lung cancer surgery: A case report. (April 2023) - Li, Yuting; Luo, Yuxiang; Fu, Guang; Ge, Mingjian; Tie, Hongtao
Abstract: Introduction and importance: Superior mesenteric artery syndrome (SMAS) is a rare medical condition resulting from vascular compression of the third part of the duodenum in the angle between the aorta and the superior mesenteric artery, leading to partial or complete intestinal obstruction and causing a series of symptoms. We now introduce a case of SMAS after lung cancer surgery, which was unique in that it was most likely caused by weight loss after surgery. Case presentation: A 58-year-old male patient gradually developed severe nausea, vomiting, and weight loss after lung cancer surgery. A diagnosis of SMAS was made after the computed tomography of the abdomen was performed. The patient's symptoms were relieved after immediate placement of a nasojejunal nutrition tube for gastrointestinal decompression and enteral nutrition support. Clinical discussion: SMAS is rare and the symptoms are not specific, the clinical diagnosis of it is mostly confirmed by imaging. The presence of SMAS should be considered as a possibility when recurrent nausea and vomiting occur after lung surgery that excludes the above-mentioned causes. Conclusion: The signs and symptoms of SMAS are usually non-specific, which leads to misdiagnosis in all probability. SMAS should be considered when unexplained significant weight loss accompanied by recurrent nausea and vomiting happens to postoperative patients. Highlights: SMAS may be difficult to be recognized after lung surgery. SMAS is mostly confirmed by imaging. SMAS should be considered when postoperative patients have unexplained significant wasting.